Awareness and attitudes of women towards cervical cancer screeningin Oyo state, Nigeria (2014)
"Cervical cancer is one of the leading causes of cancer deaths among women especially in the developing world. This study examined the awareness and the attitude of women towards cervical cancer screening in Agbowo Primary Health Centre in Ibadan, Nigeria. Using a cross-sectional study design and convenient sampling, a questionnaire was administered to collect data from 100 women who utilised postnatal and immunization services in the health centre. The hypotheses were tested using Pearson product moment correlation at significance level of P<0.005. The findings showed that the majority (52%) of the participants were aware of cervical cancer, 58% were aware of cervical cancer screening but only 5.0% had utilised cervical cancer screening services. There was significant positive relationship (r=0.369; P=0.001) between awareness and utilisation of cervical cancer screening services and educational background and utilisation of cervical cancer screening services (P=0.002) as well as economic status and use of the screening services (r=0.276; P=0.001). Attitude and uptake of cervical cancer screening services also showed a positive correlation (r=0.276; P<0.006) some of the factors that influenced uptake include lack of awareness about where to get screened, cost, attitude of health workers and delay in hospitals. The study has shown that cervical cancer screening uptake is still very poor, although, the awareness of cervical screening was fairly high. There is no doubt that education improve uptake of cervical cancer screening. There is still the need to create more awareness and make the services available so as to improve the uptake of cervical cancer screening.